Study of Seagrass Beds Condition Nearby Waters in Mokupa Village, Tombariri District, Minahasa Regency - Lasut, Nicole Theresa; Tilaar, Sandra O.; Sondak, Calvyn F. A.; Rampengan, Royke M.; Sinjal, Chatrien A. L.; Rembet, Unstain N. W. J. (Sam Ratulangi University, 2023)
The existence of seagrass beds in a shallow water environment has an important ecological role for the organisms that depend on this ecosystem. This research was conducted with the aim of knowing the types of seagrass and the condition of the seagrass beds in the waters near Mokupa Village, where the beach is between Mokupa Resort and Lotus Resort Manado. The method used is a quadrant transect (vertically to the shoreline), the coordinates point 1°24'53